2020
DOI: 10.1163/1568539x-00003584
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid supplementation affects the post-hibernation performance of southern corroboree frogs

Abstract: Many animals hibernate to survive winter conditions, however, arousal from hibernation generates reactive oxygen species (ROS) that can cause oxidative stress. Dietary antioxidants, like carotenoids, may reduce oxidative stress during arousal from hibernation, and assist with post-hibernation recovery and performance. We tested the effect of carotenoid supplementation on exercise performance (escape-response and activity) in southern corroboree frogs (Pseudophryne corroboree) following initial arousal from hib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The effect of diet treatment (T0, T1, T2 and T3) on possible that b-carotene has no or little positive effect on exercise performance in P. corroboree, with our earlier finding that frogs benefit from consuming a mixed carotenoid supplement possibly linked to the consumption of other types of carotenoids (e.g lutein or zeaxanthin). In support of this notion, McInerney et al (2020) tested the effect of b-carotene at low and moderate doses (0.1 mg g-1 and 1 mg g-1) on larval P. corroboree burst speed and distance travelled in escape response trials, and found no evidence for enhanced performance. It is possible that P. corroboree may be unable to process and utilize b-carotene as effectively as other carotenoids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of diet treatment (T0, T1, T2 and T3) on possible that b-carotene has no or little positive effect on exercise performance in P. corroboree, with our earlier finding that frogs benefit from consuming a mixed carotenoid supplement possibly linked to the consumption of other types of carotenoids (e.g lutein or zeaxanthin). In support of this notion, McInerney et al (2020) tested the effect of b-carotene at low and moderate doses (0.1 mg g-1 and 1 mg g-1) on larval P. corroboree burst speed and distance travelled in escape response trials, and found no evidence for enhanced performance. It is possible that P. corroboree may be unable to process and utilize b-carotene as effectively as other carotenoids.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the scarcity of studies, as well as variation in types of carotenoids used across studies, further work is required to determine how carotenoids influence exploratory behavior. Furthermore, a growing body of evidence suggests that the effects of carotenoids may be highly dose dependent, and also vary depending on the physiological and behavioral traits examined (Keogh et al, 2018;McInerney et al, 2019;McInerney et al, 2020). Thus, in order to significantly advance our understanding of the effect of dietary carotenoids on exploration behavior, additional studies investigating dose responses are required.…”
Section: Introductionmentioning
confidence: 99%
“…Following arrival, all metamorphs were fed a basal diet consisting of commerciallyavailable crickets (Acheta domesticus) which are known to contain negligible levels of carotenoids (McInerney et al 2020) for five weeks until experimental diets commenced on March 15 th , 2019. Experimental diets were administered twice weekly and were prepared by dusting a standardised weight of crickets (approx.…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%
“…The southern corroboree frog is a critically endangered montane frog from the southeast Australia that is primarily under threat from the amphibian chytrid fungus. Previous studies on this species have demonstrated that carotenoid supplementation has positive yet dose‐ and carotenoid class‐dependent effects on time until metamorphosis (McInerney et al., 2019), skin colour hue and saturation (Umbers et al., 2016), physical performance (Silla et al., 2016), and escape response (McInerney et al., 2020), although it does not affect larval growth or survival (Byrne & Silla, 2017). As such, there is strong evidence that carotenoids influence the colour and physiology of this species in a way that may affect performance and viability.…”
Section: Introductionmentioning
confidence: 99%